The frequency and timing of sepsis-associated coagulopathy in the neonatal intensive care unit - Aziz, Khyzer B.; Saxonhouse, Matthew; Mahesh, Divya; Wheeler, Kathryn E.; Wynn, James L. (Frontiers in Pediatrics, 2024)
Introduction Sepsis is a common cause of morbidity and mortality in the neonatal intensive care unit (NICU). The frequency and severity of sepsis-associated coagulopathy as well as its relationship to illness severity are unclear. Methods We performed a single-center, retrospective, observational cohort study of all infants admitted to the University of Florida Health (UF Health), level IV NICU between January 1st 2012 to March 1st 2020 to measure the frequency of sepsis-associated coagulopathy as well as its temporal relationship to critical illness in the NICU population. All clinical data in the electronic health record were extracted and deposited into an integrated data repository that was used for this work. Results We identified 225 new sepsis episodes in 216 patients. An evaluation for sepsis-associated coagulopathy was performed in 96 (43%) episodes. Gram-negative pathogen, nSOFA score at evaluation, and mortality were greater among episodes that included a coagulopathy evaluation compared with those that did not. Abnormal coagulation results were common (271/339 evaluations; 80%) and were predominantly prothrombin times. Intervention (plasma or cryoprecipitate) followed a minority (84/271; 31%) of abnormal results, occurred in 40/96 (42%) episodes that were often associated with >1 intervention (29/40; 73%), and coincided with thrombocytopenia in 37/40 (93%) and platelet transfusion in 27/40 (68%). Shapley Additive Explanations modeling demonstrated strong predictive performance for the composite outcome of death and/or treatment for coagulopathy in neonates (f1 score 0.8, area under receiver operating characteristic curve 0.83 for those with abnormal coagulation values). The three most important features influencing the composite outcome of death or treatment for coagulopathy included administration of vasoactive medications, hematologic dysfunction assessed by the maximum nSOFA platelet score, and early sepsis (≤72 h after birth). Conclusions A coagulopathy evaluation was performed in a minority of NICU patients with sepsis and was associated with greater illness severity and mortality. Abnormal results were common but infrequently associated with intervention, and intervention was contemporaneous with thrombocytopenia. The most important feature that influenced the composite outcome of death or treatment for coagulopathy was the administration of vasoactive-inotropic medications. These data help to identify NICU patients at risk of sepsis-associated coagulopathy.